Carotid Intima Media Thickness as a Prognostic Marker in Chronic Coronary Syndrome Patients Undergoing PCI - N. Nashy, Baher; Samy, Mohamed; Fathy, Karim; Elbasha, Karim; MH , Alshair; Y Elnady, Khaled (Journal of Neonatal Surgery, 2025)
Chronic coronary syndrome (CCS) represents a stable yet progressive manifestation of coronary artery disease, with residual cardiovascular risk persisting despite advances in percutaneous coronary intervention (PCI) and optimal medical therapy. Accurate risk stratification remains essential to improve long-term outcomes. Carotid intima media thickness (CIMT), a noninvasive and widely available marker of subclinical atherosclerosis, has been extensively studied as a surrogate of systemic vascular disease and a predictor of cardiovascular events. This review summarizes current evidence on the prognostic value of CIMT in patients with CCS, with particular emphasis on those undergoing PCI. The relationship between carotid and coronary atherosclerosis is analyzed, emphasizing CIMT assessment methods and their connection to cardiovascular events like myocardial infarction, stroke, and mortality. CIMT is generally not recommended for the routine assessment of cardiovascular risk; however, it may become relevant and important for certain patients who have been diagnosed with CCS, as it can provide additional insights into their condition and potential treatment options.